2011
DOI: 10.1051/0004-6361/201116836
|View full text |Cite
|
Sign up to set email alerts
|

La2010: a new orbital solution for the long-term motion of the Earth

Abstract: We present here a new solution for the astronomical computation of the orbital motion of the Earth spanning from 0 to −250 Myr. The main improvement with respect to our previous numerical solution La2004 is an improved adjustment of the parameters and initial conditions through a fit over 1 Myr to a special version of the highly accurate numerical ephemeris INPOP08 (Intégration Numérique Planétaire de l'Observatoire de Paris). The precession equations have also been entirely revised and are no longer averaged … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
834
2
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 745 publications
(878 citation statements)
references
References 56 publications
37
834
2
5
Order By: Relevance
“…It allowed dating sedimentary and biological phenomena present in the section, such as the end-Maastrichtian regression and the early Danian planktonic foraminifera biozones boundaries. However, the 405-kyr eccentricity cycle, which had not been identified by HENNEBERTT & DUPUIS (2003), is better than the ~20-kyr precession and the ~100-kyr eccentricity cycles, at establishing a reliable cyclostratigraphic-based scale: because of its higher stability (LASKAR, 1999;LASKAR et al, 2004LASKAR et al, , 2011 and its duration which is closer to the time scales usually used by geologists (biozones, magnetozones). It is thus more easily correlated with those scales.…”
Section: B a Powerful Toolmentioning
confidence: 79%
See 1 more Smart Citation
“…It allowed dating sedimentary and biological phenomena present in the section, such as the end-Maastrichtian regression and the early Danian planktonic foraminifera biozones boundaries. However, the 405-kyr eccentricity cycle, which had not been identified by HENNEBERTT & DUPUIS (2003), is better than the ~20-kyr precession and the ~100-kyr eccentricity cycles, at establishing a reliable cyclostratigraphic-based scale: because of its higher stability (LASKAR, 1999;LASKAR et al, 2004LASKAR et al, , 2011 and its duration which is closer to the time scales usually used by geologists (biozones, magnetozones). It is thus more easily correlated with those scales.…”
Section: B a Powerful Toolmentioning
confidence: 79%
“…6). To clearly see the link existing between the astronomical, climatic and sedimentary signals, the first step is to examine the characteristics of the original signal as published by astronomers (LASKAR, 1988;LASKAR et al, 1993LASKAR et al, , 2004LASKAR et al, , 2011VARADI et al, 2003). …”
Section: B the Astronomical Toolmentioning
confidence: 99%
“…These parameters affect the long-term stability of both the precession and 260 obliquity solutions [Lourens et al, 2004;Husing et al, 2007]. We use the most recent 261 nominal eccentricity solution (i.e., La2011_ecc3L) [Laskar et al, 2011a[Laskar et al, , 2001bwhich was used to generate previous astronomically tuned high-resolution age models 265 for this time interval [Pälike et al, 2006a,b we match directly to minima in the La2011 eccentricity time series (Fig. 6c).…”
Section: Astronomical Target Curve 252mentioning
confidence: 99%
“…In this case climatic variations influence the transfer of the detrital argillaceous fraction, coming from the platform top or the adjacent continental areas, and the carbonate sedimentation, which is constituted by benthic, pelagic, or winnowed platform top material. It was already shown that the lithological variations, induced by the variations of the Earth's orbit parameters in the MILANKOVITCH band (periods from 20 to 400 kyr; BERGER, 1978aBERGER, , 1978bLASKAR, 1988;BERGER & LOUTRE, 1991;LASKAR et al, 2004LASKAR et al, , 2011 were appropriate to establish a very precise time scale (e.g., HERBERT & D'HONDT, 1990;ten KATE & SPRENGER, 1993;HILGEN et al, 1993HILGEN et al, , 1999HOU-SE & GALE, 1995;HERBERT, 1999;SHACKLETON et al, 1999;CLEMENS, 1999;HINNOV, 2000HINNOV, , 2005PÄLIKE et al, 2001;GALEOTTI et al, 2003;HENNE-BERT & DUPUIS, 2003;DINARÈS-TURELL et al, 2003;LOURENS et al, 2005aLOURENS et al, , 2005bFIET et al, 2006;PÄLIKE et al, 2006;SPROVIERI et al, 2006;HINNOV & OGG, 2007;WESTERHOLD et al, 2007WESTERHOLD et al, , 2008HENNEBERT et al, 2009;HENNEBERT, 2012).…”
Section: Astrochronologymentioning
confidence: 99%
“…In spite of the proven chaotic behaviour of the solar system, eccentricity periods are known to be very stable in time and have not probably significantly varied during the last 100 Ma (LASKAR, 1989(LASKAR, , 1999VARADI et al, 2003;LASKAR et al, 2004LASKAR et al, , 2011. The very stable 405-kyr eccentricity component is assumed to be adequate to tune the entire Cenozoic and Mesozoic timescale .…”
Section: Astrochronologymentioning
confidence: 99%